Mending the ozone layer: The role of transnational policy networks - Reiner Grundmann (Max-Planck-Institut für Gesellschaftsforschung, 1996)
Successful international cooperation is a puzzling problem for social scientists. The ozone layer has been subject to both international treaties and domestic leg-islation. It is one of the foremost success stories in international relations, yet insufficiently understood. In this paper I argue that existing approaches - including the sophisticated and highly acclaimed epistemic community approach - do not take the underlying theoretical problems seriously enough. Departing from the epistemic community approach, I propose a framework for a network analysis combining interests, knowledge and power into a coherent model, which is derived from this case but can apply to similar cases sharing similar characteristics. It is argued that one of two rivaling policy networks gained hegemony over the other, mainly by winning over allies from the competing network. Ultimately this contributed to the competing network's breakdown. – – Erfolgreiche internationale Kooperation ist für Sozialwissenschaftler oft ein Rätsel. Eines der erfolgreichsten Beispiele internationaler Kooperation sind die Maßnahmen zum Schutz der Ozonschicht, die auf nationaler und internationaler Ebene ergriffen wurden. Dieser Erfolg wird bislang unzureichend erklärt: vorliegende Ansätze stellen sich den theoretischen Schwierigkeiten nicht in adäquater Weise. Dies gilt auch für den Epistemic-community-Ansatz, der in letzter Zeit viel Aufmerksamkeit auf sich gezogen hat. In kritischer Auseinandersetzung mit diesem wird ein Netzwerkansatz entwickelt, in dem Macht, Interessen und Ideen als Erklärungsmomente zusammengeführt werden. Der zentrale Mechanismus, der zu internationaler Kooperation führt, besteht darin, daß es einem von zwei konkurrierenden Politikynetzwerken gelingt, Akteure aus dem gegnerischen Netzwerk herauszubrechen, wodurch dieses zerfällt. Dieser Ansatz sollte auf andere Fälle anwendbar sein, die ähnliche Eigenschaften wie der vorliegende aufweisen.
Keywords: 300